2022
DOI: 10.1111/joor.13396
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of alendronate in an experimental temporomandibular joint osteoarthritis

Abstract: Temporomandibular disorder (TMD) appears in many forms, from disturbances of the surrounding muscles to intra-temporomandibular joint (TMJ) irregularities. Depending on the habits of the patients, the stress level and the progression of the disease, these disorders can turn into TMJ osteoarthritis (TMJ-OA), which is characterised by the deterioration and degeneration of the bone and cartilage tissue in the joint. TMJ osteoarthritis is a very painful condition that negatively affects the patient's quality of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Clinical and animal studies have reported favorable results of bisphosphonates as a potential intervention option of OA treatment. ALN has been reported to be effective in reducing osteophyte formation [ 10 , 11 ] and cartilage degeneration [ 12 ] in OA. Moreover, ALN blocks OA matrix metalloproteinase-13 (MMP-13) expression and increases collagen type II (Col-II) expression to reduce OA extracellular matrix degeneration [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and animal studies have reported favorable results of bisphosphonates as a potential intervention option of OA treatment. ALN has been reported to be effective in reducing osteophyte formation [ 10 , 11 ] and cartilage degeneration [ 12 ] in OA. Moreover, ALN blocks OA matrix metalloproteinase-13 (MMP-13) expression and increases collagen type II (Col-II) expression to reduce OA extracellular matrix degeneration [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bisphosphonates are indicated for treatment of osteoporosis due to their inhibitory effects on the osteoclast-mediated bone resorption [ 29 ]. Alendronate is a nitrogen-containing bisphosphonate and potent inhibitor of osteoclastic resorption that has demonstrated positive results in preclinical models of OA after systemic and intraarticular administration [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%